Intellectual capital determinants of customer value added in a transitional economy: An unconvincing role of knowledge supportive technology - Cabrilo, Sladjana; Kianto , Aino; Dahms, Sven (International Journal of Industrial Engineering and Management, 2026)
This study investigates whether and how a firm’s utilization of knowledge management-supportive information technology (IT) moderates the effects of three-partite intellectual capital on customer value and, further, market performance. We draw on a combination of thus-far isolated literature streams namely: intellectual capital, technology-based knowledge management, and marketing to build a research model, which is tested on a survey of firms in the transitional economic context of Serbia. The survey data is analyzed using structural equation modelling–partial least squares (SEM-PLS). The results show that structural capital and relational capital have a positive effect on customer value, which further positively affects market performance. Surprisingly, IT practices may even decrease the extent to which an organization produces value for its customers by capitalizing on its intellectual capital. Our findings demonstrate that technological excellence cannot solve everything and that an optimal balance between “tech” and “human-based” resources must be found for superior customer value added. This brings an interesting nuance to the discussion concerning the interaction between knowledge resources and technological capabilities in facilitating performance. The findings also demonstrate that heavy reliance on IT-based knowledge management in certain economic contexts may backfire with respect to a firm’s customer value and eventually deteriorate its performance. Article history: Received (April 7, 2025); Revised (December 19, 2025); Accepted (December 30, 2025); Published online (February 18, 2026)